CD73‐derived adenosine and tenascin‐C control cytokine production by epicardium‐derived cells formed after myocardial infarction. Issue 7 (31st March 2017) - Hesse, Julia; Leberling, Stella; Boden, Elisabeth; Friebe, Daniela; Schmidt, Timo; Ding, Zhaoping; Dieterich, Peter; Deussen, Andreas; Roderigo, Claudia; Rose, Christine R.; Floss, Doreen M.; Scheller, Jürgen; et al.
ABSTRACT: Epicardium‐derived cells (EPDCs) play a fundamental role in embryonic cardiac development and are reactivated in the adult heart in response to myocardial infarction (MI). In this study, EPDCs from post‐MI rat hearts highly expressed the ectoenzyme CD73 and secreted the profibrotic matricellular protein tenascin‐C (TNC). CD73 on EPDCs extensively generated adenosine from both extracellular ATP and NAD. This in turn stimulated the release of additional nucleotides from a Brefeldin A‐sensitive intracellular pool via adenosine‐A2B R signaling, forming a positive‐feedback loop. A2B R activation, in addition, strongly promoted the release of major regulatory cytokines, such as IL‐6, IL‐11, and VEGF. TNC was found to stimulate EPDC migration and, together with ATPP2X7 R signaling, to activate inflammasomes in EPDCs via TLR4. Our results demonstrate that EPDCs are an important source of various proinflammatory factors in the post‐MI heart controlled by purinergic and TNC signaling.—Hesse, J., Leberling, S., Boden, E., Friebe, D., Schmidt, T., Ding, Z., Dieterich, P., Deussen, A., Roderigo, C., Rose, C. R., Floss, D. M., Scheller, J., Schrader, J. CD73‐derived adenosine and tenascin‐C control cytokine production by epicardium‐derived cells formed after myocardial infarction. FASEB J. 31, 3040–3053 (2017). www.fasebj.org